DASHBOARD SEBARAN KARTU KMILN/DIASPORA DENGAN MENGGUNAKAN PYTHON LIBRARY PANDAS, NUMPY, MATPLOTLIB DAN GRADIO: DASHBOARD FOR KMILN/DIASPORA CARD DISTRIBUTION USING PYTHON LIBRARIES PANDAS, NUMPY, MATPLOTLIB, AND GRADIO - Dana Abdulrachman; Verdi Yasin; Akmal Budi Yulianto (LPPM Universitas Abdurrab, 2026)
This management of data for the Indonesian Citizens Abroad Card (KMILN) has traditionally been presented in static table formats, making it difficult to analyze trends, monitor diaspora distribution, and generate comprehensive reports. This study aims to design an interactive KMILN/Diaspora dashboard using the prototype method to ensure an iterative development process that aligns with user needs. The dashboard was developed using Python with Pandas, NumPy, Matplotlib, and a Gradio interface to process and visualize the data. The development stages included requirement communication, rapid planning, initial design, prototype construction, testing, and refinement. The results show that the dashboard successfully displays diaspora distribution charts, growth trends, geographic mapping, and employment data interactively, supported by filtering features such as country, Indonesian missions (KBRI), and diaspora categories. The implementation of this dashboard simplifies data analysis, enhances information accuracy, and supports data-driven decision-making within the Directorate of Diaspora Affairs.